Demonstration of a compact deep UV Raman spatial heterodyne spectrometer for biologics analysis. Issue 7 (3rd May 2022) - Foster, Michael; Brooks, William; Jahn, Philipp; Hedberg, Jesper; Andersson, Andreas; Ashton, And Lorna
Abstract: Monoclonal antibodies and antibody fragments are increasingly important classes of biotherapeutics. However, these products are both challenging and expensive to manufacture. New process analytical technologies used to monitor these products during their manufacture are of significant interest. Deep UV Raman spectroscopy promises to provide the required specificity and accuracy, however instruments, have historically been large and complex. In this paper, a new deep UV Raman instrument is described using a solid‐state laser and a spatial heterodyne spectrometer. The instrument overcomes practical limitations of the technique and could readily be used for online measurement. A series of observations have been made of biopharmaceutical products, including immunoglobulin G and domain antibodies. Where high levels of both specificity and linearity when measuring samples of different concentration with a precision of better than 0.05 mg/mL has been demonstrated. Abstract : This paper describes a compact deep UV Raman instrument for the study of proteins, peptides and similar biological materials. Using a diode laser and spatial heterodyne spectrometer operating at 229 nm provides unmatched performance dealing with the issue of sample damage associated with operating in the UV. Allowing difficult samples to be probed at a range of concentrations including immunoglobulin G and tryptophan. We present concentration and specificity observations of antibody fragments.